2008
DOI: 10.1182/blood-2007-07-099648
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated action of G-CSF and ELR + CXC chemokines in neutrophil mobilization during acute inflammation

Abstract: In this study, we have identified a unique combinatorial effect of the chemokines KC/MIP-2 and the cytokine granulocyte colony-stimulating factor (G-CSF) with respect to the rapid mobilization of neutrophils from the bone marrow in a model of acute peritonitis. At 2 hours following an intraperitoneal injection of thioglycollate, there was a 4.5-fold increase in blood neutrophil numbers, which was inhibited 84% and 72% by prior administration of blocking mAbs against either the chemokines KC/MIP-2 or G-CSF, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
198
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(218 citation statements)
references
References 63 publications
17
198
0
3
Order By: Relevance
“…Our data indicate that Gr-1-positive cells become rapidly activated in response to stroke in the bone marrow, which causes the release of the CXCR2-positive myeloid population within 4 hours reperfusion. It has been shown that CXCL1 and G-CSF exert coordinated actions on neutrophil mobilisation from the bone marrow (Wengner et al, 2008). Although in our study CXCL1 was upregulated in bone marrow-derived neutrophils/monocytes after both sham and stroke surgery, our results indicate a more pronounced release of CXCL1 (at 4 hours reperfusion) and G-CSF (at 10 minutes reperfusion) into the circulation in response to stroke, which correlates with increased stroke-induced cell mobilisation from the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data indicate that Gr-1-positive cells become rapidly activated in response to stroke in the bone marrow, which causes the release of the CXCR2-positive myeloid population within 4 hours reperfusion. It has been shown that CXCL1 and G-CSF exert coordinated actions on neutrophil mobilisation from the bone marrow (Wengner et al, 2008). Although in our study CXCL1 was upregulated in bone marrow-derived neutrophils/monocytes after both sham and stroke surgery, our results indicate a more pronounced release of CXCL1 (at 4 hours reperfusion) and G-CSF (at 10 minutes reperfusion) into the circulation in response to stroke, which correlates with increased stroke-induced cell mobilisation from the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that humoural factors, including cytokines and chemokines are rapidly elevated in both the brain and the periphery after stroke (Offner et al, 2006a). In addition, we recently showed that cerebral ischaemia induces systemic upregulation of CXCL1 (KC), a chemokine that acts in concert with granulocyte-colony-stimulating factor (G-CSF) to mobilise neutrophils from the bone marrow in response to inflammatory challenges (Chapman et al, 2009;Wengner et al, 2008). The release of neutrophil granulocytes from the bone marrow is a complex process, which involves an antagonistic interaction between the neutrophil chemokine receptors CXCR2 and CXCR4 (Eash et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its positive influence on granulopoiesis, G-CSF is a well-known disruptor of neutrophil retention 42 . G-CSF pressures the bone marrow to release neutrophils through thrombopoietin (TPO)-induced upregulation of CXCR2 ligands on megakaryocytes 38 , reduction of CXCL12 expression by bone marrow stromal cells 43,44 and downregulation of CXCR4 on neutrophils themselves 45 .…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…An array of chemokines is induced by inflammation and recruits monocytes, neutrophils and other cells to sites of infection. The chemokine receptors CCR2 and CXCR2 are required for monocytes and neutrophils, respectively, to egress from the bone marrow into the blood during steady state and infection [7][8][9][10]. They are also central for monocyte and neutrophil recruitment and host survival during infections [9,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%